2013
DOI: 10.1590/s1516-89132013000200019
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, carcass characteristics and meat quality of finishing bulls fed crude glycerin-supplemented diets

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
2
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 28 publications
(46 reference statements)
14
39
2
7
Order By: Relevance
“…Despite the pH decline with advance in rigor mortis, the values obtained after 24 h of chilling can be considered adequate, since they were lower than the value considered the limit (6.0) for obtaining DFD (dark, firm, dry) meat (ALVES et al, 2005). Besides, it should be noted that the results obtained for the pH of the carcasses were consistent with those reported by Françozo et al (2013) and Egea et al (2014). These authors observed that crude glycerin levels in cattle diets did not change the pH of the carcasses after 24 h of chilling.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the pH decline with advance in rigor mortis, the values obtained after 24 h of chilling can be considered adequate, since they were lower than the value considered the limit (6.0) for obtaining DFD (dark, firm, dry) meat (ALVES et al, 2005). Besides, it should be noted that the results obtained for the pH of the carcasses were consistent with those reported by Françozo et al (2013) and Egea et al (2014). These authors observed that crude glycerin levels in cattle diets did not change the pH of the carcasses after 24 h of chilling.…”
Section: Resultssupporting
confidence: 90%
“…However, the results obtained are controversial (LAGE et al, 2010;FRANÇOZO et al, 2013). In general, animal performance is expected to improve since crude glycerin enhances the efficiency of energy utilization by the animal, as reported by Françozo et al (2013). With respect to the carcass, the inclusion of crude glycerin tends to increase the proportion of fat ( VAN CLEEF et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Water activity by thawing and cooking ranged from 5 to 8.6 and 23.2 to 29.8%, respectively. In general, those water losses for cattle finished in feedlots and slaughtered between an age of 18 and 36 months ranged from 5 to 10 and from 20 to 30%, respectively (Eiras et al, 2014;Eiras et al, 2016;Françozo et al, 2013;Rivaroli et al, 2016). Thus, the water activity by thawing and cooking observed in this study can be considered as normal.…”
Section: Water Holding Capacitymentioning
confidence: 56%
“…Mean water loss value in the carcass during chilling was 1.5%. This value is considered acceptable for the beef market in Brazil (Françozo et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…However, few studies have focused on the potential changes in meat quality and nutritional value brought about by dietary glycerin (Françozo et al, 2013;Bartoñ et al, 2013;Lage et al, 2014b). A potential effect of dietary glycerin for ruminant meat quality is the increased availability of gluconeogenic compounds, which allow for a greater deposition of intramuscular fat (Mach et al, 2009).…”
Section: Introductionmentioning
confidence: 99%